“A SURVEILLANCE, PREVENTION, IMPLEMENTATION, AND CONTROL PROGRAM OF MOTHER TO CHILD TRANSMISSION OF HEPATITIS B” - Camposano , Reygia Andes; -Arreglo , Elenita Manrique; Flores, John; Rocha , Mary Aretha; Simon , Leovenci; Nelson Maglague, Nelson x (International Journal of Psychosocial Rehabilitation, 2020)
Hepatitis B is a major public health problem in the Philippines. An estimated 7.3 million adult Filipinos (16.7% of the adult population) are chronically infected making our country hyperendemic for hepatitis B. This rate is extremely high compared to other countries and is more than double the 8% average prevalence of HBV infection in the Western Pacific region. A 2003 survey showed the prevalence of hepatitis B to be highest in the 20-49 year age group, which comprise the workforce or those entering the workforce.